The Superficial Inferior Epigastric Artery Flap and its Relevant Vascular Anatomy in Korean Women - Kim, Byung Jun; Choi, Jun Ho; Kim, Tae Hoon; Jin, Ung Sik; Minn, Kyung Won; Chang, Hak (Archives of Plastic Surgery, 2014)
Background Lower abdominal soft tissue transfer is the standard procedure for breast reconstruction. However, abdominal wall weakness and herniation commonly occur postoperatively at the donor site. To reduce the morbidities of the donor site, the superficial inferior epigastric artery (SIEA) flap was introduced, but inconsistent anatomy of the SIEA has reduced its utility. In the present study, the anatomy of the superficial inferior epigastric vessels in Korean women was determined with regards to breast reconstructive surgery.Methods The vascular anatomies of the SIEA and superficial inferior epigastric vein (SIEV) were evaluated on 32 breast cancer patients receiving free transverse rectus abdominis musculocutaneous flap reconstruction after mastectomy. The existence, pulsation, location, external diameter, and depth of the SIEA and SIEV were measured at the lower abdominal incision level.Results SIEA and SIEV were present in 48/64 (75.00%) and 63/64 (98.44%) hemi-abdomens, respectively. Pulsation of the SIEA was found in 44/48 (91.67%) cases. The mean locations of SIEA and SIEV were +5.79 (±12.87) mm, and -8.14 (±15.24) mm from the midpoint between the anterior superior iliac spine and symphysis pubis, respectively. The mean external diameters of SIEA and SIEV were 1.20 (±0.39) mm and 1.37 (±0.33) mm, and they were found at a mean depth of 9.75 (±2.67) mm and 8.33 (±2.65) mm, respectively.Conclusions The SIEA was absent in 25% of Korean women and had a relatively small caliber. Therefore, careful preoperative assessment of the lower abdominal vasculature is required to achieve successful breast reconstruction using SIEA flaps.
Keywords: Epigastric arteries; Regional anatomy; Koreans; Breast reconstruction